Potential Losses at Pt. Bank Sumut Marelan Raya Sharia Sub-Branch Against the Binding of the Deed of Mortgage Data Errors yy Ppat - Abdan Taqyanto; Tan Kamello; Hasyim Purba (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
Binding deed of mortgage that occurs data errors by PPAT, such errors as mistaken identity of the debtor / creditor, errors in the data of the collateral object and editorial errors in the mortgage clause, which can affect the legal force of the deed. Formulation of the problem causes of data errors in The Binding of the deed of mortgage by PPAT in PT. Bank Sumut Marelan Raya Syariah Auxiliary Branch. Steps that can be taken by PT. Bank Sumut to reduce the risk of data errors in The Binding of mortgage deed. The role of PPAT in ensuring data accuracy in the deed of mortgage and its responsibilities in case of data errors. This type of research is an empirical legal research, descriptive analytical.  The data sources used in this study are primary and secondary Data. Data collection techniques using library research, and field research, document study data collection tools. The research used in this study is deductive thinking method to inducti. The cause of data errors in The Binding of the deed of mortgage by PPAT in PT. Bank Sumut Marelan Raya Sharia sub-branch, namely administrative errors, such as typos in the name of the party, identity number, land area, or certificate number. Incomplete documents such as party identity documents (KTP, tin, KK) that are not in accordance or are not valid. Land certificates that are still in the process of transferring rights or there are records of blocking / disputes.